Dietary Cinnamaldehyde Enhances Growth Performance, Digestion, Immunity, and Lipid Metabolism in Juvenile Fat Greenling (Hexagrammos otakii) - Yixin Gu; Jian Han; Wenjie Wang; Yu Zhan; Huijie Wang; Wenyuan Hua; Yue Liu; Yafeng Guo; Zhuang Xue; Wei Wang (Aquaculture Nutrition)
Fat greenling (Hexagrammos otakii) is a kind of economic fish that is widely consumed by human, and its intensive farming technology is making important progress. However, high-density farming may cause the occurrence of diseases in H. otakii. Cinnamaldehyde (CNE) is a new feed additive for aquatic animals and has a positive effect on disease resistance. In the study, dietary CNE was evaluated on the growth performance, digestion, immune response, and lipid metabolism of juvenile H. otakii (6.21±0.19 g). Six experimental diets were formulated containing CNE at levels of 0, 200, 400, 600, 800, and 1000 mg/kg for 8 weeks. The percent weight gain (PWG), specific growth rate (SGR), survival (SR), and feeding rate (FR) were significantly increased by including CNE in fish diets regardless of the inclusion level (P<0.05). The feed conversion ratio (FCR) was significantly decreased among the groups fed CNE supplemented diets (P<0.05). A significant decrease in hepatosomatic index (HSI) was observed in fish fed 400 mg/kg-1000 mg/kg CNE compared to the control diet (P<0.05). Fish-fed diets containing 400 mg/kg and 600 mg/kg CNE had a higher level of crude protein in muscles than the control diet (P<0.05). Moreover, the activities of lipase (LPS) and pepsin (PEP) in the intestinal were markedly increased in juvenile H. otakii-fed dietary CNE (P<0.05). Apparent digestibility coefficient (ADC) of dry matter, protein, and lipid was significantly increased with CNE supplement (P<0.05). The activities of catalase (CAT) and acid phosphatase (ACP) in the liver were markedly enhanced by including CNE in juvenile H. otakii diets compared with the control (P<0.05). The activities of superoxide dismutase (SOD) and alkaline phosphatase (AKP) in the liver were markedly enhanced in juvenile H. otakii treated with CNE supplements 400 mg/kg-1000 mg/kg (P<0.05). Additionally, the levels of total protein (TP) in the serum were markedly increased by including CNE in juvenile H. otakii diets compared with the control (P<0.05). In the CNE200, CNE400, and CNE600 groups, albumin (ALB) levels in the serum were markedly higher compared with that in the control (P<0.05). In the CNE200 and CNE400 groups, the levels of immunoglobulin G (IgG) in the serum were significantly increased compared with that the control group (P<0.05). The juvenile H. otakii-fed dietary CNE had lower triglycerides (TG) and total cholesterol (TCHO) levels in the serum than fish-fed CNE-free diets (P<0.05). The gene expression of peroxisome proliferator-activated receptor alpha (PPAR-α), hormone-sensitive lipase (HSL), and carnitine O-palmitoyltransferase 1 (CPT1) in the liver was significantly increased by including CNE in fish diets regardless of the inclusion level (P<0.05). However, fatty acid synthase (FAS), peroxisome proliferator-activated receptor gamma (PPAR-γ), and acetyl-CoA carboxylase alpha (ACCα) in the liver were markedly decreased with CNE supplements 400 mg/kg-1000 mg/kg (P<0.05). The glucose-6-phosphate1-dehydrogenase (G6PD) gene expression levels in the liver were markedly decreased compared with the control (P<0.05). The optimal supplementation level of CNE was shown by curve equation analysis to be 590.90 mg/kg.